Undifferentiated Pleomorphic Sarcoma and the Importance of Considering the Oncogenic and Immune-Suppressant Role of the Human T-Cell Lymphotropic Virus Type 1: A Case Report - Lupo, Sergio; Berini, Carolina; Cánepa, Camila; Santini Araujo, Eduardo; Biglione, Mirna (Frontiers in Oncology, 2017)
Introduction: Soft-tissue sarcomas account for 0.7 % of all malignant tumors, with an incidence rate of 3 per 100,000 persons/year. The Undifferentiated Pleomorphic Sarcoma (UPS) with giant cells, a high grade tumor of soft tissue, is very unusual, especially in young adults before the age of 40. Human T-cell lymphotropic virus type-1 (HTLV-1) is a human retrovirus, classified as group 1 human carcinogens by The International Agency for Research on Cancer (IARC), that causes an aggressive malignancy known as adult T-cell lymphoma/leukemia (ATLL) and a progressive chronic inflammatory neurological disease named HTLV-1 associated myelopathy/ tropical spastic paraparesis (HAM/TSP). HTLV-1 causes accumulation of genetic mutations in the host genome that could contribute to cellular transformation, one of the oncogenic features of HTLV-1. Case report: We describe a case of a young woman with UPS who suffered from HAM/TSP with 3 years of evolution. In 2013, the patient started with neurological symptoms: weakness in the legs and bladder dysfunction. One year later, the patient developed a mild paraparesis in both extremities, anti-HTLV-1 antibodies were detected in plasma and in cerebrospinal fluid (CSF), and HAM/TSP was confirmed. In November 2015, a benign ganglion cyst was firstly suspected without intervention and by March 2016 a sarcoma was diagnosed. Three weeks after surgical resection, the tumor aroused in deep tissue and behaved aggressively, implicating a curative wide resection of the fibula, joint reconstruction and soft tissue graft. Histopathological examination confirmed UPS with giant cells. Concluding remarks: The unapparent subclinical immunodeficiency state due to HTLV-1 infection deserves to be considered in order to carefully monitor the possibility of developing any type of cancer. Besides, reaching an accurate and timely diagnosis of UPS can be challenging due to the difficulty in diagnosis/classification and delayed consultation. In this particularly case, considering the high grade of UPS and the progressive invalidating myelopathy caused by HTLV-1, treatment should be carefully evaluated to positively impact on the patient's life expectancy.